Coronavirus Disease-19 (Covid-19) Pandemic Response Through The Universal Defense: The Role Of Intelligence - Atam; Pujo Widodo; Helda Risman (Technium Social Sciences Journal, 2020)
The COVID-19 pandemic that began in Wuhan China has threatened the safety and affected all aspects of human life throughout the world both in European, American, African, Middle Eastern, Australian and Asian countries including Indonesia. The problem of the epidemic cannot yet be fully addressed by the World Health Organization (WHO) so that all countries in the world competing to find a vaccine to tackle the outbreak. The latest development of a case that has been declared a pandemic by World Health Organization (WHO) last March shows that more than 4 million people have been infected with fatalities of nearly three hundred thousand people in more than two hundred countries. This condition then gave rise to the question in the public how the role of state institutions in responding to threats to public security, especially the intelligence sector, whose information is not widely known to the public. The purpose of this study is to analyze the role of Intelligence in tackling the COVID-19 pandemic within the framework of the defence of the Indonesian universe. Role theory is the author’s analysis instrument to spell out the description of the role and importance of Intelligence in tackling the COVID-19 pandemic. This research is written in a qualitative methodology using a phenomenological approach and data collected from interviews and documentation studies. This research concludes that Intelligence has a real and significant role in the level of identification and detection of outbreaks and their impact so that it becomes a vital input in the formulation of policies relevant to the country in responding to the pandemic.